ANALISIS LOCATION QUOTIENT (LQ) PADI DI KOTA LANGSA - Imas Ameliya; Silva Anzitha; Faoeza Hafiz Saragih (MEDIAGRO, 2020)
The problem of this research is which sub-district in Langsa City is the Base for Rice Crops. The aim of this research is to identify the Subdistrict which is the base area for Rice Plants in Langsa City. The method used in this research is a survey method based on secondary data. The results showed that the greater the Sub-District rice production compared to the City production, the more likely the area would be a Basis Sub-District. LQ value analysis shows that East Langsa Sub-District, Langsa Lama Sub-District and West Langsa Sub- District are classified as Basis. Keywords: Langsa City, Location Quotient, Rice Crops